Hydrometrocolpos from diagnosis to fatal consequences - Marjaneh Farazestanian; Ezat Hajmollarezaei; Maryam Mirzaeian (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Anomaly scan is one of the most important findings that can be followed up during pregnancy. Abdominal masses of the fetus, which have different origins depending on the location and sex of the fetus, can be recognized in these examinations. One of the rarest masses that are seen in 0.1% of term female babies is hydrometrocolpos. Case report: A 38-year-old female patient with a gestational age of 36 weeks and 5 days, with a history of previous caesarean section and membrane ruptured, is undergoing cesarean section. Due to the previous child suffering from mental retardation and microcephaly in this pregnancy, a delayed anomaly ultrasound is recommended and an abdominal mass with the possibility of hydrometrocolpos is diagnosed. After birth, the abdominal mass is aspirated due to respiratory distress and drained several times during care. Due to frequent fevers and the diagnosis of sepsis, the child dies after one month. Conclusion: During the visit of pregnant mothers, the history, family history of parents and other children should be taken into account. In some genetic disorders checking the karyotype of the parents and the fetus does not help, and depending on the specific disorder, the genetic status must be checked. Findings in the family should be checked, which requires cooperation with genetic experts and examination of the patient from that point of view